MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 3 JAKARTA PUSAT - Dikson Silitonga (JURNAL LENTERA BISNIS, 2024)
This research aims to analyze the management of educational facilities and infrastructure at the Vocational High School (SMK) Negeri 3 Jakarta Pusat. Educational facilities and infrastructure are crucial components in achieving effective and efficient learning processes. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results indicate that the management of facilities and infrastructure at SMK Negeri 3 Jakarta Pusat has been carried out quite well, but there are still some challenges that need to be addressed. The processes of planning, procurement, maintenance, and evaluation of facilities and infrastructure have followed the existing procedures, although their implementation has not been optimal. Supporting factors include the commitment of the school administration and support from the local government. Meanwhile, inhibiting factors consist of budget limitations, lack of participation from some stakeholders, and technical issues in facility maintenance. This research suggests that the school should enhance coordination with the government and private sector to obtain more adequate budget support. Additionally, there needs to be an improvement in the capacity of facility and infrastructure management personnel, as well as the development of continuous training programs. Regular evaluations and stricter supervision are also expected to improve the quality of facilities and infrastructure management at SMK Negeri 3 Jakarta Pusat.